2008
DOI: 10.1111/j.1365-2125.2008.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the pharmacokinetics of intravenous busulphan given as a single daily dose to paediatric blood or marrow transplant recipients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • The pharmacokinetics of oral busulphan given four times daily has been extensively studied. • Large inter‐ and intravariability in oral busulphan exposure has led to attempts at pharmacokinetic monitoring. • However, there have been limitations in the pharmacokinetic analysis due to inadequate characterization of the elimination phase in a 6‐h dosing interval, due to late absorption in some patients. • Intravenous (i.v.) busulphan is a relatively new administration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 40 publications
5
39
0
3
Order By: Relevance
“…18,29,30 Despite these improvements, inter-patient variability still exists and the percentage of patients reaching the target AUC after the first dose remains low. 8,18,26,31,32 Several factors have been identified to account for differences such as sex, weight, age or BSA. 4,26,33 In this paper, we examined whether the polymorphisms in the GSTA1, GSTM1 and GTP1 genes also contributed to this variability.…”
Section: Discussionmentioning
confidence: 99%
“…18,29,30 Despite these improvements, inter-patient variability still exists and the percentage of patients reaching the target AUC after the first dose remains low. 8,18,26,31,32 Several factors have been identified to account for differences such as sex, weight, age or BSA. 4,26,33 In this paper, we examined whether the polymorphisms in the GSTA1, GSTM1 and GTP1 genes also contributed to this variability.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 BU metabolism is affected by GST enzyme activity, which is influenced by age, disease condition and co-medication. 2,[12][13][14] Body weight and body surface area have been also shown to contribute to PK variability. [15][16][17][18][19] Nevertheless, a large proportion of BU variability remains unexplained 20 and could be due to GST polymorphisms influencing GST activity [21][22][23][24][25] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…BU in children. Tran et al 12 obtained a BU clearance of 4.49 ml/min per kg for patients younger than 6 years of age and 3.35 ml/min per kg for those older than 6 years; Schechter et al 41 estimated that BU clearance is 3.8 ml/min per kg in children younger than 4 years versus 3.0 ml/min per kg in those older than 4 years; Nath et al 42 demonstrated a linear decrease in BU clearance from 4.8 ml/min per kg in infancy to 3.3 ml/min per kg at 10 years and to 2.0 ml/min per kg at 20 years; and Vassal et al 35 reported a clearance of 3.7 ml/min per kg in early infancy, 4 ml/min per kg at 1 year of age and a linear decline to about 2.3 ml/min per kg in adulthood. We found that the younger patients have not only a higher BU clearance but also a less predictable PK profile.…”
Section: Discussionmentioning
confidence: 99%